Odpowiedź :
Odpowiedź:
zad 1
a)
2x + 6 = 12
2x = 12 - 6 = 6
x = 6/2 = 3
sprawdzenie
2 * 3 + 6 = 12
6 + 6 = 12
12 = 12
L = P
b)
3y - 4 = 17
3y = 17 + 4 = 21
y = 21/3 = 7
sprawdzenie
3 * 7 - 4 = 17
21 - 4 = 17
17 = 17
L = P
c)
4 - 2x = 10
- 2x = 10 - 4 = 6
2x = - 6
x = - 6/2 = - 3
sprawdzenie
4 - 2 * (- 3) = 10
4 + 6 = 10
10 = 10
L = P
d)
x + 6 = 2x + 3
x - 2x = 3 - 6
- x = - 3
x = 3
sprawdzenie
3 + 6 = 2 * 3 + 3
9 = 6 + 3
9 = 9
L = P
zad 2
a)
x - 47 = 49
x = 49 + 47 = 96
sprawdzenie
96 - 47 = 49
49 = 49
L = P
b)
x - 39 = 18
x = 18 + 39 = 57
sprawdzenie
57 - 39 = 18
18 = 18
L = P
c)
x + 12 = 132
x = 132 - 12 = 120
sprawdzenie
120 + 12 = 132
132 = 132
L = P
d)
5x = 35
x = 35/5 = 7
sprawdzenie
5 * 7 = 35
35 = 35
L = P
e)
4 : y = 11
4 = 11 * y = 11y
y = 4/11
sprawdzenie
4 : 4/11 = 11
4 * 11/4 = 11
11 = 11
L = P
f)
t : 14 = 0
t = 14 * 0 = 0
sprawdzenie
0 : 14 = 0
0 + 0
L = P
g)
8x = 64
x = 64/8 = 8
sprawdzenie
8 * 8 = 64
64 = 64
L = P
h)
4x + 5 = 29
4x = 29 - 5 = 24
x = 24/4 = 6
sprawdzenie
4 * 6 + 5 = 29
24 + 5 = 29
29 = 29
L = P
Zadanie 1
a) 2x + 6 = 12 Sprawdzenie:
2x = 12 - 6 2*3 + 6 = 12
2x = 6 /:2 6 + 6 = 12
x = 3 12 = 12
b) 3y - 4 = 17 Sprawdzenie:
3y = 17 + 4 3*7 - 4 = 17
3y = 21 /:3 21 - 4 = 17
y = 7 17 = 17
c) 4 - 2x = 10 Sprawdzenie:
-2x = 10 - 4 4 - 2*(-3) = 10
-2x = 6 /:(-2) 4 - (-6) = 10
x = -3 10 = 10
d) x + 6 = 2x + 3 Sprawdzenie:
x - 2x = 3 - 6 3 + 6 = 2*3 + 3
-x = -3 9 = 6 + 3
x = 3 9 = 9
Zadanie 2
a) x - 47 = 49 Sprawdzenie:
x = 49 + 47 96 - 47 = 49
x = 96
b) x - 39 = 18 Sprawdzenie:
x = 18 + 39 57 - 39 = 18
x = 57
c) x + 12 = 132 Sprawdzenie:
x = 132 - 12 120 + 12 = 132
x = 120
d) 5x = 35 /:5 Sprawdzenie:
x = 7 5*7 = 35
e) 4 : y = 11 Sprawdzenie:
[tex]\frac{4}{y} = 11[/tex] /*y [tex]4 : \frac{4}{11} = 11[/tex]
4 = 11y [tex]4 * \frac{11}{4} = 11[/tex]
11y = 4 /:11 [tex]\frac{44}{4} = 11[/tex]
y = [tex]\frac{4}{11}[/tex] 11 = 11
f) t : 14 = 0 Sprawdzenie:
[tex]\frac{t}{14} = 0[/tex] /*14 0 : 14 = 0
t = 0
g) 8x = 64 /:8 Sprawdzenie:
x = 8 8*8 = 64
h) 4x + 5 = 29 Sprawdzenie:
4x = 29 - 5 4*6 + 5 = 29
4x = 24 /:4 24 + 5 = 29
x = 6 29 = 29